INDONESIAN STUDENTS’ DIFFICULTIES IN PRONOUNCING ENGLISH DIPHTONGS - Donal, Andri (JEE (Journal of English Education), 2016)
One of Indonesian students' difficulties in learning English is pronouncing English sounds correctly. Indonesian language as mother tongue influences significantly to the way of Indonesian students in pronouncing English sounds. Compared to English, Indonesian language generally does not have differences between spelling the letter and pronouncing the sounds. Among all English sounds, diphthongs are assumed as one of the most difficulties pronounced by Indonesian students. This study was conducted to thirty five students of University of Pasir Pengaraian, Riau Province by using mix method where the researcher gave test to find out students’ difficulties in pronouncing English diphthongs and observation to describe the factors influencing students’ difficulties in pronouncing English diphthongs. The result of study showed that the most difficult of English diphthong was [аυ] sound. Factors influencing students have difficulties in pronouncing English diphthongs were mother language interfere, lack of knowledge in English sound systems and unsuccessful in using borrowed English words. This study is expected can give contribution in improving Indonesian students pronunciation especially diphthong sounds.